Fumarate hydratase FH c.1431_1433dupAAA (p.Lys477dup) variant is not associated with cancer including renal cell carcinoma. Issue 1 (3rd September 2019) - Zhang, Liying; Walsh, Michael F.; Jairam, Sowmya; Mandelker, Diana; Zhong, Yi; Kemel, Yelena; Chen, Ying‐Bei; Musheyev, David; Zehir, Ahmet; Jayakumaran, Gowtham; Brzostowski, Edyta; Birsoy, Ozge; et al.
Abstract: Fumarate hydratase ( FH ) mutations underpin the autosomal recessive syndrome. FH deficiency and the autosomal dominant syndrome hereditary leiomyomatosis and renal cell carcinoma (HLRCC). The FH c.1431_1433dupAAA (p.Lys477dup) genomic alteration has been conclusively shown to contribute to FH deficiency when occurring with another FH germline alteration. However, a sufficiently large dataset has been lacking to conclusively determine its clinical significance to cancer predisposition in the heterozygous state. We reviewed a series of 7, 571 patients with cancer who received germline results through MSK‐IMPACT testing at the Memorial Sloan Kettering Cancer Center. The FH c.1431_1433dupAAA (p.Lys477dup) variant was detected in 24 individuals, none of whom was affected with renal cancer. Eleven of the 372 patients with renal cancer were identified to carried pathogenic FH variants associated with HLRCC. None of these 372 patients with renal cancer carried the FH c.1431_1433dupAAA variant. Our data indicate the FH c.1431_1433dupAAA is not associated with cancer including renal cell carcinoma.